Evaluation of government funding support for national priority development related to the environmental sector in regions - Andi Setyo Pambudi (Universitas Pakuan, 2023)
Sustainable development focusing on environmental issues is the target of both central and local governments. Ideally, planning and funding this issue requires harmonizing and implementing top-down and bottom-up alignment. Neglect from a regional point of view often causes various obstacles in implementation, which of course, causes inefficiency. The allocation and distribution of budgeting through special transfer funds for environmental issues are interesting to elaborate with attention to the sustainability of the policy and the expected benefits. The analysis of the implementation of government funding support for the development of national priorities related to the environmental sector in the region is interesting to be elaborated more deeply to provide information on strategic control and integration of future development. This further elaboration is in line with the national economic recovery after the COVID-19 pandemic, which has attracted the attention of many parties. The method used in the analysis is a qualitative approach through literature review and limited discussion (FGD) with stakeholders at the central-regional level and through online survey methods. The literature review uses previous research, journals, books, and planning documents at the central and regional levels to capture the Physical SAF 2021 policy for the environment, analyze budget distribution, and analyze central-regional planning/funding alignment in terms of planning documents. Focus Group Discussion (FGD) method and online questionnaires are used to capture field problems. Expectations desired in this evaluation-based analysis can provide recommendations following the actual conditions in the area as the implementer of this fund.Pembangunan berkelanjutan yang berfokus pada isu lingkungan menjadi target pemerintah baik pusat maupun daerah. Idealnya, perencanaan dan pendanaan masalah ini membutuhkan harmonisasi dan implementasi top-down dan bottom-up. Pengabaian dari sudut pandang daerah seringkali menimbulkan berbagai kendala dalam pelaksanaannya, yang tentunya menimbulkan inefisiensi. Alokasi dan distribusi penganggaran melalui dana transfer khusus untuk masalah lingkungan hidup menarik untuk dijabarkan dengan memperhatikan kesinambungan kebijakan dan manfaat yang diharapkan. Analisis pelaksanaan dukungan pendanaan pemerintah untuk pembangunan prioritas nasional terkait bidang lingkungan hidup di daerah menarik untuk dielaborasi lebih dalam guna memberikan informasi pengendalian strategis dan keterpaduan pembangunan ke depan. Penjelasan lebih lanjut ini sejalan dengan pemulihan ekonomi nasional pasca pandemi COVID-19 yang menjadi perhatian banyak pihak. Metode yang digunakan dalam analisis adalah pendekatan kualitatif melalui kajian pustaka dan diskusi terbatas (FGD) dengan pemangku kepentingan di tingkat pusat dan daerah serta melalui metode survei online. Tinjauan literatur menggunakan penelitian sebelumnya, jurnal, buku, dan dokumen perencanaan di tingkat pusat dan daerah untuk menangkap kebijakan SAF Fisik 2021 untuk lingkungan, menganalisis distribusi anggaran, dan menganalisis keselarasan perencanaan/pembiayaan pusat-daerah dalam hal dokumen perencanaan. Metode Focus Group Discussion (FGD) dan kuesioner online digunakan untuk menjaring permasalahan lapangan. Harapan yang diinginkan dalam analisis berbasis evaluasi ini dapat memberikan rekomendasi sesuai dengan kondisi aktual di daerah selaku pelaksana dana ini.